Radical N-cyanation of sulfoximine through acetonitrile CCN cleavage. Issue 50 (16th December 2015) - Hu, Weiming; Teng, Fan; Peng, Haibo; Yu, Jintao; Sun, Song; Cheng, Jiang; Shao, Ying
Graphical abstract: Abstract: A new strategy for the N-cyanation of sulfoximine via radical process has been developed, leading to the desired products in moderate to excellent yields with good functional group tolerance. This procedure provided an alternative pathway to CCN bond activation of acetonitrile. In particular, 1, 1, 3, 3-tetramethylguanidine also worked well in this procedure.